2002
DOI: 10.1038/nature00841
|View full text |Cite
|
Sign up to set email alerts
|

A plant receptor-like kinase required for both bacterial and fungal symbiosis

Abstract: Most higher plant species can enter a root symbiosis with arbuscular mycorrhizal fungi, in which plant carbon is traded for fungal phosphate. This is an ancient symbiosis, which has been detected in fossils of early land plants. In contrast, the nitrogen-fixing root nodule symbioses of plants with bacteria evolved more recently, and are phylogenetically restricted to the rosid I clade of plants. Both symbioses rely on partially overlapping genetic programmes. We have identified the molecular basis for this con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
550
0
23

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 824 publications
(589 citation statements)
references
References 25 publications
16
550
0
23
Order By: Relevance
“…SymRK is believed to function in both NF perception and downstream signal transduction, and is required for the earliest detectable root hair responses (Endre et al, 2002;Stracke et al, 2002). However, little is known about how SymRK transduces the NF signal to downstream components.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SymRK is believed to function in both NF perception and downstream signal transduction, and is required for the earliest detectable root hair responses (Endre et al, 2002;Stracke et al, 2002). However, little is known about how SymRK transduces the NF signal to downstream components.…”
Section: Discussionmentioning
confidence: 99%
“…japonicus SymRK is known to play a role in IT initiation (Stracke et al, 2002). We scored IT numbers in SIE3 RNAi hairy roots 8 d after rhizobial inoculation.…”
Section: Suppression Of Rhizobial Infection By Sie3 Rnaimentioning
confidence: 99%
See 1 more Smart Citation
“…DOES NOT MAKE INFECTION2 [DMI2] in M. truncatula, NORK in alfalfa, and SYM19 in pea). At the same time, the ortholog of L. japonicus (called symbiosis receptor-like kinase, or SYMRK), which is located in a syntenic region of M. truncatula, alfalfa, and pea, also was isolated (Stracke et al, 2002(Stracke et al, , 2004.…”
Section: Cross-species Gene Prediction and Isolationmentioning
confidence: 99%
“…6 Symbiosis Receptor Kinase (SYMRK), an upstream LRR-RLK of the Nod factor signaling pathway, is indispensible for nodule organogenesis. 21,22 Recently, we have demonstrated that overexpression of the intracellular kinase domain of SYMRK (SYMRK-kd) from M. truncatula or Arachis hypogaea in M. truncatula roots induces nodule organogenesis in the absence of rhizobia. 23 Spontaneous nodulation in presence of SYMRK-kd was 6-fold more than rhizobia induced nodulation supported by full length SYMRK in M. truncatula TR25 (symrk knock out) roots suggesting the importance of SYMRK ectodomain in regulating nodule number.…”
mentioning
confidence: 99%